Fundamentals of Optical Computing Technology Forward the Next Generation Supercomputer - Li, Xiujian (Springer Singapore, 2018)
This book presents the principles, experimental technologies, up-to-date research findings and applications of various optical-computing technologies and devices. It also discusses semiconductor multiple quantum well (MQW) photoelectronic devices, vertical-cavity surface-emitting lasers (VCSELs), lasers, micro optical elements and diffractive optical elements, optical storage, optical parallel interconnections, and optical-buffer technology as the main technologies for optical computing. Furthermore, it explores the potential of optical-computing technology. It offers those involved in optical design, photonics, and photoelectronic research and related industries insights into the fundamentals and theories of optical computing, enabling them and to extend and develop the functions of fundamental elements to meet the requirement of optical-computing systems.